Simultaneous odour-face presentation strengthens hedonic evaluations and event-related potential responses influenced by unpleasant odour. (13th April 2018) - Cook, Stephanie; Kokmotou, Katerina; Soto, Vicente; Wright, Hazel; Fallon, Nicholas; Thomas, Anna; Giesbrecht, Timo; Field, Matt; Stancak, Andrej
Highlights: Pleasant and unpleasant odours modulated ratings of neutral faces. Unpleasant odour had a greater effect on ratings of faces presented simultaneously. Faces shown during unpleasant odour stimulation evoked greater cortical responses. Abstract: Odours alter evaluations of concurrently presented visual stimuli, such as faces. Stimulus onset asynchrony (SOA) is known to affect evaluative priming in various sensory modalities. However, effects of SOA on odour priming of visual stimuli are not known. The present study aimed to analyse whether subjective and cortical activation changes during odour priming would vary as a function of SOA between odours and faces. Twenty-eight participants rated faces under pleasant, unpleasant, and no-odour conditions using visual analogue scales. In half of trials, faces appeared one-second after odour offset (SOA 1). In the other half of trials, faces appeared during the odour pulse (SOA 2). EEG was recorded continuously using a 128-channel system, and event-related potentials (ERPs) to face stimuli were evaluated using statistical parametric mapping (SPM). Faces presented during unpleasant-odour stimulation were rated significantly less pleasant than the same faces presented one-second after offset of the unpleasant odour. Scalp-time clusters in the late-positive-potential (LPP) time-range showed an interaction between odour and SOA effects, whereby activation was stronger for faces presented simultaneously with the unpleasant odour, compared to the same faces presented after odour offset. Our results highlight stronger unpleasant odour priming with simultaneous, compared to delayed, odour-face presentation. Such effects were represented in both behavioural and neural data. A greater cortical and subjective response during simultaneous presentation of faces and unpleasant odour may have an adaptive role, allowing for a prompt and focused behavioural reaction to a concurrent stimulus if an aversive odour would signal danger, or unwanted social interaction.